Efecto de piro y metafosfatos de sodio en suelos de Costa Rica - FASSBENDER, H.W. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Two experiments were carried out on tropical soils with different acidity (pH CaCl2 4,1 and 5,2, respectively), applying in increasing doses (0, 88, 175 and 350 ppm P) of triple superphosphate, sodium pyro-and metaphosphate; their effect was observed on the production of dry matter and P absorption by tomato and ryegrass. Under conditions of high acidity, apparently the hydrolysis of the condensed phosphates was very low and although an increase in production took place, this was not comparable to triple superphosphate. Under light acidity the effect of the pyro- and metaphosphate was more favorable but still less than that of triple superphosphate.